Pengaruh Kohesivitas Kelompok dan Motivasi Kerja terhadap Kinerja Biro Sumber Daya Manusia, Organisasi, dan Tata Laksana, Sekretariat Kabinet - Listyarini, Dien (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The Bureau of Human Resources, Organization, and Administration (SDMOT) of the Cabinet Secretariat experienced a performance decline in 2018, with personnel services decreasing by 6.98%, training utilization decreasing by 7.77%, and satisfaction with personnel service output decreasing by 7.71%. This decline is suspected to be due to a lack of group cohesiveness and work motivation among SDMOT employees. The purpose of this research is to determine the impact of group cohesiveness and work motivation on the performance of the SDMOT Bureau. This study uses a quantitative approach. Validity testing was conducted using expert judgment, discrimination power using the item-total correlation analysis technique, and reliability using Cronbach's alpha variance analysis, while data analysis used multiple regression techniques. The results show a very strong relationship between group cohesiveness and performance. The adjusted R2 value of group cohesiveness on performance is 0.644, which means that group cohesiveness contributes 64.4% to performance. Work motivation has a significantly positive effect on performance. The adjusted R2 value is 0.678, indicating that work motivation contributes 67.8% to performance. Together, group cohesiveness and work motivation on performance are seen from the correlation coefficient (R) of 0.861, which shows a very strong relationship between the independent variables of group cohesiveness and work motivation with the dependent variable performance. The combined contribution of group cohesiveness and work motivation to performance is 72.7%, while 27.3% is influenced by other variables outside the study.